2014
DOI: 10.5005/jp-journals-10026-1158
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia: Substitute for Metal Ceramics

Abstract: In the search for the ultimate esthetic restorative material, many all-ceramic systems have been proposed. Dental research is nowadays directed toward metal-free prosthetic restorations in order to improve an esthetical outcome of crown and bridge restorations. Zirconia is a polycrystalline ceramic without a glassy phase and exists in several forms. Zirconia cores for fixed partial dentures (FPD) on anterior and posterior teeth and on implants are now available. This article is a review of zirconia crowns as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…As such the reaction rate can be easily controlled, and it is possible to obtain a narrow nanoparticle size distribution 26 . Reverse micelle microemulsions are transparent, isotropic, and thermodynamically stable 27,28 In continuation to our earlier research work 29,30 , present work reports synthesis of ZnO nanoparticles by microemulsion route. Characterization of ZnO nanoparticles were carried out by XRD, TEM, DSC, FTIR and UV-Visible spectroscopy.…”
Section: Introductionsupporting
confidence: 56%
“…As such the reaction rate can be easily controlled, and it is possible to obtain a narrow nanoparticle size distribution 26 . Reverse micelle microemulsions are transparent, isotropic, and thermodynamically stable 27,28 In continuation to our earlier research work 29,30 , present work reports synthesis of ZnO nanoparticles by microemulsion route. Characterization of ZnO nanoparticles were carried out by XRD, TEM, DSC, FTIR and UV-Visible spectroscopy.…”
Section: Introductionsupporting
confidence: 56%
“…The current study suggested the use of zirconia meshwork to reinforce the acrylic denture base, this hypothesis was in agreement with Takano and Sakurai 7 who stated that zirconia had advantageous properties to be used in denture bases, and Kumar et al 6 who claimed that CAD/CAM manufacturing of zirconia reduced its cyclic fatigue failure, however, and in agreement with the results of this study, Bashi and Al-Nema 9 found that the Co-Cr meshworks provided the best reinforcement of denture bases when compared to any other material as also proven by the work of Resin 10 on the metal reinforcement of denture bases.…”
Section: Discussionsupporting
confidence: 90%
“…1 A claim has been made that at least 2 mm thickness of acrylic resin should exist at these fracture sites to provide resistance against fracture, 2 however, the use of a metal framework to reinforce the denture bases was found more efficient in two-implant assisted overdentures to counteract the effect of the cantilever distal to the abutments. [3][4][5] Zirconia was recently suggested to replace metals in dental prostheses, and improve the mechanical properties of complete denture bases, 6,7 where its addition in nano particles form improved the transverse strength of the heat polymerized denture bases, 8,9 however, still the addition of cobalt chromium meshes or stainless-steel wires produced better fracture resistance. 10 The combination of nano-zirconia, titanium dioxide and other several organic and inorganic fillers was shown to increase the impact and flexural strength as compared to non-reinforced acrylic resins.…”
Section: Whethermentioning
confidence: 99%
“…In continuation to our earlier research work 29,30 , present work reports synthesis of ZnO nanoparticles by microemulsion route. Characterization of ZnO nanoparticles were carried out by XRD, TEM, DSC, FTIR and UV-Visible spectroscopy.…”
Section: Introductionmentioning
confidence: 55%